Determinants of antenatal care and skilled birth attendance services utilization among childbearing women in Guinea: evidence from the 2018 Guinea Demographic and Health Survey data - Ahinkorah, Bright O; Seidu, Abdul-Aziz; Agbaglo, Ebenezer; Adu, Collins; Budu, Eugene; Hagan, John E; Schack, Thomas; Yaya, Sanni (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Globally, maternal health remains a major priority. Most of maternal deaths globally occur in sub-Saharan Africa, with most of these deaths linked to lack of access to antenatal care and skilled assistance during delivery. This study assessed the determinants of antenatal care and skilled birth attendance services utilization among childbearing women in Guinea. Methods Data for this study were obtained from the 2018 Guinea Demographic and Health Survey (GDHS). Data of 4,917 childbearing women were considered as our analytical sample. The outcome variables for the study were utilization of antenatal care and skilled birth attendance. Analysis was carried out using chi-square tests and multivariable logistic regression. Results The results showed that women aged 15-24 (AOR=1.29, CI=1.03-1.62), women who had secondary/higher level of education (AOR=1.70, CI=1.33-2.19), and those whose partners had secondary/higher level of education (AOR=1.46, CI=1.22-1.75), women in the richest wealth quintile (AOR=5.09, CI=3.70-7.00), those with planned pregnancies (AOR=1.50, CI=1.23-1.81), Muslim women (AOR=1.65, CI=1.38-2.12), those who take healthcare decisions alone (AOR=1.53, CI=1.24-1.89), and those who listened to radio less than once a week (AOR= 1.30, CI=1.10-1.53) had higher odds of antenatal care uptake. Also, women with secondary/higher level of education (AOR=1.83, CI=1.25-2.68), those whose partners had secondary/higher level of education (AOR=1.40, CI=1.11-1.76), those in the richest wealth quintile (AOR=10.79, CI=6.64-17.51), those with planned pregnancies (AOR=1.25, CI=1.03-1.52), Christian women (AOR=4.13, CI=3.17-5.39), those living in urban areas (AOR=3.00, CI=2.29-3.94), women with one birth (AOR= 1.58, CI=1.20-2.06), those who take healthcare decisions alone (AOR=1.87, CI=1.46-2.39), those who read newspaper at least once a week (AOR= 1.19, CI=1.01-1.40), those who watched television at least once week (AOR=1.69, CI=1.30-2.19), and those in female-headed households (AOR=1.52, CI=1.20-1.92) were more likely to utilize the services of skilled birth attendants. Conclusion The study proved that various socio-economic and contextual factors influence antenatal care and skilled birth attendance in Guinea. These findings suggest the need to design community-based interventions (e.g., miniature local ANC clinics, early screening services) that prioritize women’s education and vocational training, media accessibility, especially among the poor, and those residing in rural settings. Such interventions should not ignore the influence of other socio-cultural norms that hinder the utilization of antenatal care and skilled birth attendance services in Guinea.